Efeitos do treinamento hipóxico intermitente sobre variáveis hematológicas e capacidade de performance - Geller, César Alcides (2005)
The goal of the present study aimed at the assessment of the influences of intermittent hypoxic training (IHT) sessions on haematological parameters, aerobic capacity (AC), and running performance (RP), under hypoxic and normoxic conditions. The group of study was constituted by nine (09) volunteers of Military Pentathlon Athletes, male sex, with mean ages of 23 years old (23 ± 3,6). These athletes underwent (pre-) and post-testing measurements of maximum effort in normoxyc and hypoxic conditions - 13% O2 (simulated altitude 3.800 meters). In the course of the research work hemograms, cardiac frequency, blood lactate concentration [lact], haemoglobin oxygen saturation, the index of perception of effort and ergospirometry variables were fully measured and analysed. The assessments were done in twenty-nine (29) sessions of IHT, with 13% of oxygen concentration (one hour, five times a week). The statistics analyses using the Wilcoxon test showed a significant decrease in the number of erythrocytes and MCHC (p< 0,05). No changes were noticed in the blood lactate concentration [lact], cardiac frequency (FC) and in the maximum VO2 in normoxyc conditions. However, there was an expressive reduction of the [lact] in different running velocities in hypoxic (5, 4, 7, 2, 9, 0, 10, 8, 12,6 km/h / p<0,05). It was also observed a significant increase in the distance running in normoxyc and hypoxic (p<0,05), and a decrease of the running time in hypoxic. In conclusion, the dosage of IHT applied in this study was efficient to increase the performance under normoxyc and hypoxic conditions, in spite of a significant reduction in the numbers of the erythrocytes and a low decrease in the hematocrits numbers. The result in hypoxic showed also that this method can be used at sea level as an alternative of preparation for high-altitude competitions.